Emerging Trends in Hypoglycemia Management and Interventions among Patients with Diabetes Mellitus - Nian Afrian Nuari; Efa Nur Aini (International Journal of Health and Medicine, 2026)
Hypoglycemia persists as a significant and frequent complication in individuals with diabetes mellitus, resulting in clinical, psychological, and economical repercussions that may hinder adequate glycemic regulation. This bibliometric analysis aimed to identify new trends in the management and interventions of hypoglycemia, with a specific focus on digital health technologies, patient education, self-management, and evidence-based preventive methods. Data were extracted from the Scopus database utilising the keywords “hypoglycemia” AND “diabetes mellitus.” The analysis encompassed 1,281 articles and reviews in English published from 2015 to 2025. Bibliographic data were refined and analysed utilising VOSviewer version 1.6.20 to investigate keyword co-occurrence, thematic clustering, and temporal overlay patterns. A minimum criterion of five papers per keyword was implemented to enhance map relevance and clarity. The findings revealed nine principal thematic clusters encompassing paediatric and adolescent populations, clinical trials, patient knowledge and behaviour, pregnancy and gestational diabetes, professional healthcare roles, dietary strategies, trial methodology, digital health applications, and school-based preventive education. High-frequency and emerging keywords reflect an increasing focus on continuous glucose monitoring, family-centered education, structured educational programmes, smartphone applications, and digital self-management assistance. The literature indicates a transition from traditional clinical treatment to multidimensional, personalised, and technology-enhanced hypoglycemia management. This study's originality is found in its comprehensive mapping of nascent research trajectories and overlooked gaps. Future interventions must integrate digital tools, organised teaching, dietary guidance, and tailored self-management assistance for at-risk diabetes populations across various international clinical and community care environments.